EFIKASI ANTI IL-6 RECEPTOR MONOCLONAL ANTIBODY SEBAGAI TERAPI ADJUVAN PASIEN COVID-19 DENGAN CYTOKINE RELEASE SYNDROME: Sebuah Tinjauan Sistematis - Shofiyah Hasya (2022)
Introduction: Cytokine release syndrome (CRS) take an important role in the progression of acute respiratory distress syndrome or multi-organ damage in severe COVID-19 patients. Several studies stated interleukin 6 including the main cytokine in the occurrence of CRS. We are interested in assessing anti-IL-6 receptor monoclonal antibodies, such as tocilizumab and sarilumab, which have potential as immunomodulators in adjuvant therapy for COVID-19 patients. Methods: We reviewed relevant Randomized Controlled Trial (RCT) studies from PubMed, Google Scholar, and EBSCO MEDLINE up to December 2021. The primary outcome included the requirement for invasive mechanical ventilation/other organ life-support, with the secondary outcome was incidence of adverse events. The risk of bias of each study was assessed using the Cochrane Risk-of-Bias Tool for Randomized Trials (RoB 2). Results: Sixteen RCT studies met the eligibility criteria involving 6,762 patients. There was an association between anti IL-6 receptor monoclonal antibodies and the requirement for IVM/other organ life support (602/3641 [16.5%] in the intervention group vs 777/3394 [23%] in the control group, RR = 0.77; 95% CI [0.72, 1.21]; P < 0.00001; I2 = 20%). There were no serious adverse events associated with the treatment. Conclusion: Anti-IL-6 receptor monoclonal antibodies are potentially safe and reduce the requirement for intubation when given concomitantly with steroids in COVID-19 patients with CRS. However, further recommendations of anti-IL-6 receptor monoclonal antibodies for COVID-19 patients, particularly sarilumab, should continue to be corroborated by high-quality evidence from randomized controlled trials. Keywords: COVID-19, Cytokine Release Syndrome, Monoclonal Antibody, Interleukin 6 (IL-6)